Success model for the G2B system / Dr. Erne Suzila Kassim, Sri Fatiany Abdul Kader Jailani and Hanitahaiza Hairudin - Kassim, Erne Suzila; Abdul Kader Jailani, Sri Fatiany; Hairudin, Hanitahaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This project aims for developing a model for quantifying the government to business system success, which specifically measuring the antecedents and its outcomes. Transparency, service performance, information quality and efficiency are the measured success, while system compatibility, user's attitude, organizational learning, supplier expectation and mimetic pressure are found to influence the coordination and transaction processes between the government and the business. The model serves as a guideline for developing and formulating a policy for IT-based government systems and application.